A review of integrating AI-based chatbots into flipped learning: new possibilities and challenges - Lo, Chung Kwan; Hew, Khe Foon (Frontiers in Education, 2023)
This mini review examines the emerging concept of integrating AI-based chatbots into flipped learning and its potential to enhance students’ learning experience. We investigate the design and practice of chatbot-supported flipped learning, as well as the benefits and challenges associated with this approach. Despite an extensive database search, only 10 empirical articles were found, indicating that this cutting-edge research topic requires further exploration. The findings of this review suggest that this emerging instructional approach could result in benefits such as increased student interaction with learning content, improved class preparation, and data-driven teaching and learning. However, potential challenges included limited technical functionality, lacking authenticity, and insufficient student motivation. The review offers insights into future research and development to advance the knowledge and practice of integrating AI chatbots into flipped learning.